GDG635 : Contemporary design issues / College of Creative Arts - UiTM, College of Creative Arts (Universiti Teknologi MARA (UiTM), 2022)
This course introduce in depth understanding of issue related to contemporary graphic design. Student will be introduced to appropriate research methodologies and apply the skills and knowledge to significance design projects. The course will be conduct in 2 ways communication with student been given ample time for independent study while been guide by the lecturer. Assessment will be based on individual project,